Analysis of Price and Brand Awareness on Consumer Purchasing Decisions in Food Stalls Businesses - Hermawan, Vivian; Sherdani, Sherdani; Angelica, Yemima; Tanis, Jonathan; Mulyandi, M. Rachman (PT. Riset Press International, 2026)
The development of the culinary industry in Indonesia shows a significant increase, including food stalls. The wide variety of food choices makes consumers more selective and consider various factors before deciding to buy. Two factors considered influential in purchasing decisions are price and brand awareness. This study aims to analyze how price and brand awareness influence consumers' purchasing decisions in the food stalls business. The method used is qualitative research with a literature study approach, through a review of five journal articles relevant to the research topic. The results show that both price and brand awareness significantly influence consumers' purchasing decisions. Competitive prices that are in line with product quality can increase purchasing interest, while strong brand awareness can build trust and encourage customer loyalty. The implication is that businesses need to set the right pricing strategy and strengthen their brand identity to increase consumer purchasing decisions.